Pengaruh Dosis Pupuk Urea Terhadap Pertumbuhan dan Hasil Padi Pada Sistem Salibu: Pengaruh Dosis Pupuk Urea Terhadap Pertumbuhan dan Hasil Padi Pada Sistem Salibu - Tri Wibowo, Wahyu; Paiman (Fakultas Pertanian, Universitas Tunas Pembangunan Surakarta, 2025)
This study aimed to determine the effect of urea fertilizer dosage on the growth and yield of Salibu rice using the Inpari 42 Agritan GSR variety. The experiment was conducted in a paddy field arranged in a completely randomized design (CRD) with a single factor consisting of four levels of urea fertilizer dosage: control, 7.5 g/clump, 15 g/clump, and 22.5 g/clump, each replicated three times. Observed parameters included plant height, number of tillers, panicle length, total dry weight, total dry grain weight, 1,000 filled grain weight, and shoot dry weight. The results showed that the application of 15 g/clump of urea was the optimal treatment for increasing total dry grain weight and the weight of 1,000 filled grains. Meanwhile, a dosage of 22.5 g/clump resulted in the highest average shoot dry weight. Quadratic regression analysis indicated an optimal dosage of 22.04 g/clump for total dry grain weight and 13.80 g/clump for the weight of 1,000 filled grains. It is recommended that further studies focus on testing urea fertilizer dosages within the predictive optimum range to validate the quadratic regression model under various agroecological conditions.